Determining Stunting Risk Areas Using a Combined AHP-GIS approach: A Case Study of Pesawaran Regency, Lampung, Indonesia - Yushananta, Prayudhy; Ahyanti, Mei (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2025)
Considering the highly detrimental future impacts of stunting, a risk map is needed. It will serve as a basis to design stunting control strategies. This study aims to determine stunting risk areas by combining the Analytical Hierarchy Process (AHP) and Geographic Information System (GIS). This study used ecological design, with a case being studied was Pesawaran Regency, Lampung Province. All secondary data were aggregate, and used sub-districts as spatial boundaries. Study variables comprised access to safe drinking water, healthy sanitation, exclusive breastfeeding, complete immunization, diarrhea, number of health facilities, fourth visit during pregnancy (ANC-K4), and child growth and development monitoring. The map was developed by employing Weighted Sum Overlay (WSO) technique. Determining weights involving multiple criteria was conducted by using AHP. The AHP yielded weighted values for each variable, namely exclusive breastfeeding (22.9%), ANC-K4 (14.4%), monitoring of child growth and development (11.7%), access to safe drinking water (11.0%), diarrhea (10.8%), number of health facilities (10.1%), complete basic immunization (10.1%), and healthy sanitation (9.0%). WSO technique revealed that three out of eleven sub-districts were included in the high-risk category for stunting (Tegineneng, Kedondong, and Padang Cermin). Meanwhile, the remaining areas were included in the medium category (Way Khilau, Marga Punduh, and Punduh Pedada) and low category (Negara Katon, Gedong Tataan, Way Lima, Way Ratai, and Teluk Pandan). GIS and AHP methods were applied to determine stunting risk areas. Areas with a high risk of stunting category are Tegineneng, Kedondong, and Padang Cermin. Suggested fundamental programs to control stunting are improvement in exclusive breastfeeding, ANC-K4 visit, monitoring of children growth and development, access to drinking water, and prevention of diarrhea.